Long‐term safety and efficacy of stenting on correcting internal jugular vein and cerebral venous sinus stenosis - Chaobo Bai; Zhiying Chen; Yuchuan Ding; Xunming Ji; Junliang Yuan; Ran Meng (Annals of Clinical and Translational Neurology, 2023)
Abstract Objectives To compare the long‐term safety and efficacy of stenting in correcting cerebral venous sinus stenosis (CVSS) and internal jugular venous stenosis (IJVS). Methods Patients confirmed with CVSS or IJVS by imaging were enrolled in this real‐world study from 2014 through 2021. Clinical characteristics and long‐term outcomes of these two diseases entities post‐stenting were followed up and compared. Results Three hundred and nineteen patients were enrolled in this study, with a mean age of 48.83 years and a BMI of 25.08 on average. In which, 144 patients underwent stenting, the stenotic segments were corrected and the venous blood flow was restored immediately post‐stenting. At 6.15 ± 1.67 days follow‐up, significant improvement was observed in headache, tinnitus, insomnia, ICP, and mean pressure gradient in both groups (all p < 0.05). At 30.53 ± 4.41 months follow‐up post‐stenting, the headache, tinnitus, visual loss, papilledema, and insomnia were attenuated remarkably or even completely disappeared. The Frisen papilledema grade scores declined from 2 (0–4) to 1 (0–3) in IJVS group and from 4 (1–5) to 1 (0–4) in CVSS group compared to the baseline. One hundred and twenty‐seven out of the 144 patients (95.5%) maintained sufficient blood flow verified by followed up computed tomographic venography or contrast‐enhanced magnetic resonance angiography. Adverse events related to stenting included three cases of intraluminal restenosis and three cases of in‐stent thrombosis, no intracranial hemorrhage, venous thromboembolisms, stent‐adjacent stenosis, and stent displacement occurred. Interpretation Using stents to correct IH and related neurological issues has shown to be a safe and effective approach for both IJVS and CVSS.